Personality Patterns of Teacher Trainees from a Malaysian Training College - Yaakub, Noran Fauziah (1990)
This study reports on the personality profile of a group of teacher trainees from a Malaysian teachers'training college for the different sexes, entry qualifications and ethnic groups. Cattell's 16 P. F. Test (Form A) was used to measure personality traits of the trainees. Results showed significant differences between male and female students on nine out of the 16factors; and between SPM and SPTM students on three factors. A comparison of the three ethnic groups revealed seven trait differences. The overall personality profile is "average" except for four factors, indicating the presence of emotional instability, pessimism, suspicion and worry.